Stakeholder’s Perspectives on Competency Based Pharmacy Education Development in India: Current Status and Future directions - Salahudeen, Sultan Muhammad; Hasan, Muhammad; Hathi, Muzibunnisa Begam Abdul; Sultan, Hiba; Sulaiman, Jasimudeen; Gousuddin, Mohammad; Rao, Avanapu Srinivasa (Research journal of pharmacy and technology, 2025)
The pharmacy profession has evolved globally from traditional product-focused roles to patient-centred healthcare services. In India, while pharmacy education has made strides in various sectors, patient-oriented services remain insufficient, highlighting the need for competency-based education (CBE) aligned with international standards. To investigate stakeholder perspectives on competency-based pharmacy education in Southern India and understand barriers to implementation, with specific focus on the International Pharmaceutical Federation (FIP) developmental goal number 5 regarding competency development. An exploratory cross-sectional qualitative survey was conducted among pharmacy professionals across various sectors. Data was collected through web-linked open-ended questionnaires distributed via email, using purposeful and snowball sampling. Thematic analysis was employed following FIP Goal 5 framework, incorporating both deductive and inductive approaches. The study included 28 participants from diverse pharmacy sectors, with 57.1% male and 42.9% female respondents. Key themes emerged around workforce development, practice enhancement, and scientific advancement. Stakeholders identified critical gaps in current pharmacy education, including insufficient practical training, limited industry exposure, and outdated curriculum designs. The findings highlighted the need for integrating modern technologies, enhancing clinical training, and developing structured assessment tools. Participants emphasized the importance of balancing theoretical knowledge with practical applications and suggested implementing a comprehensive wellness program for pharmacy professionals. The study reveals significant opportunities for reforming pharmacy education in India to meet global standards while addressing local healthcare needs. Recommendations include curriculum modernization, increased industry collaboration, and enhanced practical training. Implementation challenges identified include time constraints, insufficient trained staff, lack of public awareness, and regulatory barriers. These findings provide valuable insights for educational institutions and policymakers in developing a robust, competency-based pharmacy education system in India.